2000
DOI: 10.1080/0954412007071
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model of quality management methods and evaluating their effects on business performance

Abstract: To cite this article: Zhihai Zhang (2000) Developing a model of quality management methods and evaluating their effects on business performance, Total Quality Management, 11:1, 129-137, ABSTRACT From an extensive review of the total quality management (TQM) literature, a model of quality management methods (QMMs) was developed. The model has 83 QMMs which are categorized by the 11 TQM elements they primarily aim to improve. Ten manufacturing companies which were renowned for quality management in the Netherlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 10 publications
6
116
0
7
Order By: Relevance
“…Customer focus is defined as the extent to which an organization continuously satisfies customer needs and expectations (Zhang, 2000). Customer focus is vital that leaders encourage the understanding of customer needs, build relationships with customers and fulfill their demands (Cai, 2009).…”
Section: Tqm Practicesmentioning
confidence: 99%
“…Customer focus is defined as the extent to which an organization continuously satisfies customer needs and expectations (Zhang, 2000). Customer focus is vital that leaders encourage the understanding of customer needs, build relationships with customers and fulfill their demands (Cai, 2009).…”
Section: Tqm Practicesmentioning
confidence: 99%
“…Employees should be regarded as valuable, long-term resources worthy of receiving education and training throughout their career (Zhang, 2000). Educating and training all employees provides the information they need on the mission, vision, direction, and strategy of the organization as well as the skills they need to secure quality improvement and resolve quality problems (Tenner and DeToro, 1992).…”
Section: Training and Educationmentioning
confidence: 99%
“…Recognition and reward activities in organizations should effectively stimulate employee commitment to quality improvement activities otherwise these activities are failures and working condition improvements, salary promotions, position promotions, financial awards for excellent suggestions are good methods for recognition and reward (Zhang, 2000).…”
Section: Reward and Recognitionmentioning
confidence: 99%
“…Therefore, bearing in mind that experience has shown that some firms fail when they implement TQM (Boje and Winsor, 1993;Spector and Beer, 1994) and the implementation of TQM cannot be successful without the use of suitable quality management methods (Sitkin, Sutcliffe and Schoroeder, 1994;Wilkinson et al, 1998;Zhang, 2000) such as statistical techniques (Stuart, Mullins and Drew, 1996), managers of ISO 9000-certified small and medium firms that really want to progress towards a TQM culture, should implement the following factors, using the following methods: − Specialized training. Training cannot stop at an initial level, and must be of a continued nature (Ishikawa, 1985).…”
Section: Implications For Managersmentioning
confidence: 99%